Ways of Improving Current Assets in the System of Financial Management in Com-panies Producing Beverage - Baboyan, Khachatur (Bulletin of Yerevan University G: Economics, 2022)
The ensuring of sustainable growth rates in manufacturing companies is directly dependent on the effective financial management solutions. One of the important directions in this regard is the effective control of current assets and the development and application of new and qualitatively different approaches to financial management thereof. In the course of their day-to-day activity, the management staff of a commercial organization is forced to make right decisions within the scope of operational management, by addressing a number of key issues, the most important of which is the targeted and equitable use of resources. The regulation of the demand for working capital is a complex process, which requires appropriate reasonings. Besides, it is necessary to take into account the peculiarities of the sector of activity and the technological peculiarities of the organization. The effective solution to the problem of securing own current assets is very important in terms of financial stability of commercial organizations in crisis situations. This is directly related to the process of management of working capital requirements and is logically linked to the structure of financing sources. For the efficient management of current assets in beverage producing companies, new solutions are needed in terms of collection of accounts receivable and increase in the efficiency of control over them. In this article, by emphasizing the role of management of current assets in the overall financial management system, we have put forward ways for improvement on the basis of theoretical and practical studies made by us.
Keywords: working capital; current assets; turnover; route; receivables; operating phase; financial management; commercial organization; inventory